Influence of Biopsy Gleason Score on the Risk of Lymph Node Invasion in Patients With Intermediate-Risk Prostate Cancer Undergoing Radical Prostatectomy - Wenzel, Mike; Preisser, Felix; Hoeh, Benedikt; Welte, Maria N.; Humke, Clara; Wittler, Clarissa; Würnschimmel, Christoph; Becker, Andreas; Karakiewicz, Pierre I.; Chun, Felix K. H.; Mandel, Philipp; Kluth, Luis A. (Frontiers in Surgery, 2021)
Objective: To analyze the influence of biopsy Gleason score on the risk for lymph node invasion (LNI) during pelvic lymph node dissection (PLND) in patients undergoing radical prostatectomy (RP) for intermediate risk prostate cancer (PCa). Material and Methods: We retrospectively analyzed 684 patients, who underwent RP between 2014-06/2020 due to PCa. Univariable and multivariable logistic regression, as well as binary regression tree models were used to assess the risk of positive LNI and evaluate the need of PLND in men with intermediate risk PCa. Results: Of 672 RP eligible patients, 80 (11.9%) men harbored low-risk, 32 (4.8%) intermediate risk with international society of urologic pathologists grade (ISUP) 1 (IR-ISUP1), 215 (32.0%) intermediate risk with ISUP 2 (IR-ISUP2), 99 (14.7%) intermediate risk with ISUP 3 (IR-ISUP3) and 246 (36.6%) high-risk PCa. Proportions of LNI were 0%, 3.1%, 3.7%, 5.1% and 24.0% for low-risk, IR-ISUP1, IR-ISUP 2, IR-ISUP-3 and high-risk PCa, respectively (p<0.001). In multivariable analyses, after adjustment for patient and surgical characteristics, IR-ISUP1 (hazard ratio [HR] 0.10, p=0.03), IR-ISUP2 (HR 0.09, p<0.001) and IR-ISUP3 (HR 0.18, p<0.001) were independent predictors for lower risk of LNI, compared to men with high-risk PCa disease. Conclusion: ISUP grade significantly influence the risk of LNI in patients with intermediate- risk PCa. The risk of LNI only exceeds 5% in men with IR-ISUP3 PCa. In consequence, the need for PLND in selected patients with IR-ISUP 1 or IR-ISUP2 PCa should be critical discussed.